Effect of Gamma Irradiation on Microbial Quality and Physicochemical Attributes of Tilapia (Oreochromis niloticus) - Indra Mustika Pratama; Ashri Mukti Benita; Aldi Mujiyanto; Bani Fadhilah Akbar; Sumi Hudiyono; Irawan Sugoro (Al-Kauniyah: Jurnal Biologi, 2026)
Tilapia (Oreochromis niloticus) is a widely consumed freshwater fish commodity that is highly susceptible to microbial spoilage, leading to rapid quality deterioration and a short shelf life. Gamma irradiation is a promising preservation technology to address this issue. This study aimed to evaluate the effectiveness of gamma irradiation in reducing microbial contamination and maintaining the physicochemical quality of fresh tilapia. Samples were irradiated at a dose of 3 kGy (dose rate 1 kGy/h) in combination with vacuum packaging and refrigeration. Microbiological analyses included total plate count, Salmonella–Shigella, and total mold and yeast, while physicochemical parameters comprised pH, ash, fat, protein, water activity (aw), total volatile base nitrogen (TVB-N), trimethylamine (TMA-N), and color (L*, a*, b*), using non-irradiated samples as controls. The results showed that irradiation reduced total bacteria and Salmonella–Shigella by approximately 2 log cycles and eliminated molds and yeasts without significant changes (P >0.05) in physicochemical parameters compared to control samples. These findings indicate that gamma irradiation at 3 kGy is effective in improving microbial safety while preserving the physicochemical quality of fresh tilapia.